Odpowiedź :
Odpowiedź:
a)
w(x) = - 2x² + mx³ - 4x² + 5
Za x wstawiamy (- 3) i wartość wielomianu musi się równać (- 4)
- 4 = - 2 * (- 3)² + m * (- 3)³ - 4 * (- 3)² + 5
- 4 = - 2 * 9 - 27m - 4 * 9 + 5
- 4 = - 18 - 27m - 36 + 5
- 4 = - 27m - 49
27m = - 49 + 4
27m = - 45
m = - 45/27 = - 5/3 = - 1 i 2/3
b)
w(x) = 3x⁴ + mx³ + 2x² - 10
Za x wstawiamy (- 2) i wartość wielomianu musi się równać 6
6 = 3 * (- 2)⁴ + m * (- 2)³ + 2 * (- 2)² - 10
6 = 3 * 16 - 8m + 2 * 4 - 10
6 = 48 - 8m + 8 - 10
6 = 46 - 8m
8m = 46 - 6
8m = 40
m = 40/8 = 5